Irrigation management processes and conditions: a case study of Sri Lanka's Walawe Irrigation Improvement Project - Nijman, C. (International Irrigation Management Institute, 1991)
The detailed study of irrigation management processes and managerial conditions presented in this paper is part ofIIMI' s effort to integrate a management perspective into the assessment of irrigation performance. This management perspective requires an amalgamation of two key disciplines involved in irrigation management, irrigation engineering and management science, into an analytical framework for irrigation management. Irrigation engineering approaches are thereby evaluated by their contribution to the actual decision- making processes during system planning and design, and system operation. Yet, in the analysis of the most relevant decision-making processes, conceptual contributions of other disciplines such as economics, sociology and agronomy have to be considered as well.